Sosialisasi tentang Pentingnya Perilaku Hidup Bersih dan Sehat (PHBS) Sejak Dini di TK Yarsi Mataram - Inayati, Rizqa; Widani Darma Isasih; Ika Putri Fitri Ajiani (Insan Kreasi Media, 2023)
Clean and Healthy Living Behavior (PHBS) from an early age in kindergarten children is very important to socialize. This is intended to educate kindergarten children about the importance of implementing PHBS in their daily activities. The introduction of PHBS at an early age is the ideal time to provide education so that the hope can be recorded in memory so that it becomes a habit until adulthood. There are many types of PHBS, one of which is washing your hands properly and correctly. This socialization activity aims to increase the knowledge of children at Yarsi Mataram Kindergarten about the importance of Clean and Healthy Living Behavior (PHBS) in children, as well as providing an understanding of the simple application of Clean and HealthyLiving Behavior. The results of the service are in the form of understanding and increasing awareness of kindergarten children about the importance of developing clean and healthy living habits that are easy for them to understand, such as how to wash their hands properly and correctly. So it is hoped that this simple understanding can become a habit for them to apply until they grow up.